A Phase I and Pharmacokinetic Study of Ecteinascidin-743 on a Daily × 5 Schedule in Patients with Solid Malignancies - Miguel A. Villalona-Calero; S. Gail Eckhardt; Geoffrey Weiss; Manuel Hidalgo; Jos H. Beijnen; Charlotte van Kesteren; Hilde Rosing; Elizabeth Campbell; Maura Kraynak; Luis Lopez-Lazaro; Cecilia Guzman; Daniel D. Von Hoff; et al. (Clinical cancer research, 2002)
Purpose: The purpose of this study was to ( a ) assess the feasibility of administering ecteinascidin-743 (ET-743), a novel DNA minor-groove disrupting agent of marine origin, administered as a daily i.v. infusion for 5 days every 3 weeks; ( b ) recommend a dose for Phase II studies; ( c ) characterize its pharmacokinetic behavior; and ( d ) seek preliminary evidence of anticancer activity. Experimental Design: Patients with advanced solid malignancies were treated with escalating doses of ET-743 as a daily 1-h i.v. infusion for 5 days every 3 weeks. Plasma and urine were sampled on both days 1 and 5 of the first course. Pharmacokinetic parameters were related to the principal toxicities. Results: Forty-two patients were treated with 118 courses of ET-743 at doses ranging from 6 to 380 μg/m 2 /day. Elevations in hepatic transaminases were common at ET-743 dose levels ≥216 μg/m 2 /day, resolved rapidly, and were never dose limiting nor cumulative. Instead, hematological toxicity was the principal toxicity that precluded dose escalation. The maximum tolerated dose of ET-743 that could be administered repetitively was 325 μg/m 2 /day. Antitumor activity was noted in three patients with leiomyosarcoma and primary peritoneal and ovarian carcinomas. The pharmacokinetics of ET-743 were dose independent, and drug accumulation over the 5 days of treatment was modest, with the ratio of the area under the plasma- versus -time curve on day 5 to that on day 1 averaging 2.05. The volume of distribution at steady state was large (mean, 1037 liters/m 2 ), and the mean terminal half life on day 5 was 26.81 h. Conclusions: The maximum tolerated dose of ET-743 that can be administered repetitively is 325 μg/m 2 /day daily × 5 every 3 weeks, which is recommended for disease-directed clinical trials. The acceptable toxicity profile of ET-743 on the divided-dose schedule evaluated in this trial, as well as the generally superior antitumor activity associated with divided-dose schedules in preclinical studies, provides a rationale for further evaluation of ET-743 on this administration schedule.